An Analysis of UAV Security and Privacy Concerns of Communication Systems - Hassan, Farah Alaa A.; Almamoori, Hiba Rashid; Al-Msarhed, Nuha Kareem Hameed (Universitas Ahmad Dahlan, 2025)
Wireless communication is one of the fastest-growing research fields, with Unmanned Aerial Vehicles (UAVs) increasingly deployed as mobile router points in high-traffic areas such as bus stations, metro stations, and airport terminals to address connectivity challenges. However, despite their utility, UAVs face significant security and privacy risks. This paper presents a comprehensive analysis of these vulnerabilities through a systematic four-level classification: sensor, communication, software, and hardware. For each level, we examine (1) common weaknesses exploitable by malicious actors, (2) potential threats to civilian UAV applications, (3) active and passive attacks compromising security and privacy, and (4) possible countermeasures to mitigate such risks. Additionally, we summarize key findings on UAV security and privacy issues and highlight critical unresolved challenges. Finally, we propose future research directions, including the use of fuzzy logic to optimize drone routing by dynamically relocating UAVs to low-activity zones based on fuzzy rule-based decisions.